Efficacy of mucus regulation therapy in acute sinusitis - A. I. Kryukov (Медицинский совет, 2013)
Inflammatory diseases of the paranasal sinuses are one of the most actual problems of modern otorhinolaryngology. 15 to 36% of in-patients at ENT units are people suffering from sinusitis. In 2007, the European Academy of Allergology and Clinical Immunology (EAACI) and the European Rhinologic Society (ERS) signed the fundamental document that contains the guidelines for the treatment of rhinosinusitis and nasal polyps - the EPOS (European Position Paper on Rhinosinusitis and Nasal Polyposis). The EPOS relies on a strict evidence-based approach; however, the number of controlled studies of efficacy of drugs, even those with registered indications, was not really big. After treatment experience was accumulated by 2012, the "herbal preparations" group was included in the list of those recommended by the EPOS.